The ratioed image film thickness meter. (10th May 2018) - Husen, Nicholas M; Liu, Tianshu; Sullivan, John P
Abstract: A technique for measuring the thickness of a fluorescent oil film is presented. Incident light is cast upon the oil film and the intensity of the luminescent signal from the fluorescent dye is ratioed with the intensity of the incident light which is scattered from the surface of the model. The quotient is independent of the intensity of the incident light and proportional to the film thickness. Experiments are presented supporting that for sufficiently thin films the ratio is independent of the intensity of the incident light as well as independent of the angle from which the experiment is imaged and the angle from which the incident light is cast.